How Malaysians view the sales and service tax increment: the role of knowledge of SST and spending behaviour - Mohd Allif Anwar Abu Bakar; Sharifah Milda Amirul; Saizal Pinjaman; Oscar Dousin (Faculty of Business, Economics and Accountancy Universiti Malaysia Sabah, 2024)
The recent 2% increase in Malaysia’s Sales and Services Tax (SST) in various sectors has sparked public discussion and debates. This study aims to create a conceptual framework for the effect of knowledge of SST and spending behaviour towards acceptance of SST increment in Malaysia. The proposed framework may aid future research in providing valuable insights into how taxpayers perceive and respond to the SST changes. Besides, there is a critical need to investigate whether the SST increment would create similar responses among taxpayers regarding their perceptions of whether it is fair for taxpayers from different states of economics to pay for the SST and the taxpayer’s knowledge, and spending behaviour regarding this tax policy shift.